Endoplasmic reticulum stress mediates the myeloid-derived immune suppression associated with cancer and infectious disease - Xiaoli Lou; Deyong Gao; Liyuan Yang; Yue Wang; Yanqiang Hou (Journal of Translational Medicine, 2023)
Abstract Myeloid-derived suppressor cells (MDSCs), which are immature heterogeneous bone marrow cells, have been described as potent immune regulators in human and murine cancer models. The distribution of MDSCs varies across organs and is divided into three subpopulations: granulocytic MDSCs or polymorphonuclear MDSCs (G-MDSCs or PMN-MDSCs), monocytic MDSCs (M-MDSCs), as well as a recently identified early precursor MDSC (eMDSCs) in humans. Activated MDSCs induce the inactivation of NK cells, CD4+, and CD8+ T cells through a variety of mechanisms, thus promoting the formation of tumor immunosuppressive microenvironment. ER stress plays an important protecting role in the survival of MDSC, which aggravates the immunosuppression in tumors. In addition, ferroptosis can promote an anti-tumor immune response by reversing the immunosuppressive microenvironment. This review summarizes immune suppression by MDSCs with a focus on the role of endoplasmic reticulum stress-mediated immune suppression in cancer and infectious disease, in particular leprosy and tuberculosis.